ABDOMINAL ACTINOMYCOSIS - PEKANAN, Patchrin; RANGSITPOL, Thitiporn (The ASEAN Journal of Radiology, 2023)
Two cases of abdominal actinomycosis was presented. In one case, the disease involved ileocecum and appendix of a 35-year-old man. Plain film and ultrasonography was suggestive of localized inflammation of the ileocecal area and not specific. In another case, the disease involved left ovary with fistula tract to the anterior abdominal wall. CT scan showed left ovarian mass and soft tissue lesion at anterior parietal peritoneal cavity and muscle of right anterior lower abdominal wall.